Visitors' perceptions of the quality of services provided at the Vaal River Carnival and the relationship with satisfaction and future behavioural intentions - Rachoene, Tlake Phillemon (Vaal University of Technology, 2022)
Carnival events as tourist and visitors’ destinations are developing and promoting the cultural and heritage services of the people as a mean of attracting and enhancing life experiences. The recognition of carnival events as tourist and visitors’ destinations is evidenced by the increase in the number of carnival events held recently in the Vaal Triangle. To this end, the Vaal River Carnival presents over 15 exciting events ensuring that potential tourists and investors experience the Vaal River, historic sites, state of the art hotels, conference facilities, other business and leisure facilities. In addition, it profiles the easy access of the Vaal’s road infrastructure with far less traffic congestion in comparison to other cities within the Gauteng province. The first Vaal River Carnival was held in 2002 and attracted an audience of more than 10,000 visitors and tourists of every colour, race, age, and background together in celebration of the beauty, history, and richness of the Vaal Triangle. The success was made possible by the partnership between the Emfuleni Local Municipality, the Vaal Community, NGOs, Parastatals, and other Non-Governmental organisations. The parties came together with the sole purpose of joint marketing and profiling the Vaal Triangle as one of the best tourist and investment destinations. However, there is growing evidence that the majority of the attendees have lodged verbal complaints to carnival management, or present their complaints via print or electronic media about the service quality, management, planning and organization of facilities utilized at the event. This assertion seems true because the attendees have different perceptions and experiences which may influence a carnival revisit. Therefore, this study investigates the perceptions of visitors to the Vaal River Carnival on satisfactions regarding the quality of services provided at the event and their future behavioural intentions towards revisiting the place again. To attain the theorical objectives, the study considered the convergence of three behavioural theories while conducting a literature review to assess the influence of service quality on customer satisfaction and its effect on future behavioural intentions. To achieve the empirical objectives of the study, a quantitative research methodology was adopted and the respondents were selected using a non-probability convenience sampling technique. For data collection, the researcher used a structured self-administered questionnaire survey. Of the 400_ distributed questionnaires, the researcher utilized 323 usable questionnaires for data analysis. The Statistical Package for Social Sciences (SPSS) version 26.0 was used to compute both descriptive and inferential statistics (which includes exploratory factor analysis, correlations and regression analysis). In addition, the reliability and validity analysis were carried out in relation to the measuring instrument. Through regression analysis, positive significant predictive relationships were found between service quality and customer satisfaction (β=+.821, t value=30.490, at p<.001) as well as customer satisfaction with future behavioural intention (β=+.754; t value = 20.947 at p<0.001). The recommendations emanating from the study include the integration of an effective events development strategy in the organisation’s overall marketing strategy. Both practitioners and academics should consider the list of factors presented here in attempting to generate a greater degree of service quality among carnival settings, as well as implementing image marketing (promoting the sense of place) and destination marketing (selling the service) strategies. The limitations of the study and the suggested opportunities for further research are also identified.
M. Tech. (Department of Business Administration, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Service quality; Customer satisfaction; Future behavioural intention; Visitors; Vaal River Carnival; Dissertations, Academic -- South Africa.; Consumer satisfaction.; Customer services--Quality control.